An investigation of the impact of building orientation on energy consumption in a domestic building using emerging BIM (Building Information Modelling). (15th February 2016) - Abanda, F.H.; Byers, L.
Abstract: BIM (building information modelling) has developed into a powerful solution that can improve many aspects of construction industry. Current research regarding the impact of orientation on a building's energy needs seldom tap into the potential of BIM. This study investigates the impact of orientation on energy consumption in small-scale construction, and assesses how BIM can be used to facilitate this process. The methods adopted are three-fold. Firstly, a real-life building is modelled using Revit, one of the leading BIM tools. Secondly, through green building Extensible Markup Language, the model is exported to Green Building Studio, one of the leading energy simulation software. Thirdly, in the Green Building Studio, different building orientations are adopted and their impacts of the whole building energy are investigated. Based on the analysis of the energy consumption corresponding to the different orientations, it emerged that a well-orientated building can save a considerable amount of energy throughout its life cycle. Specifically, a total electricity use difference of 17 056 kWh and a total gas use difference of 27 988 MJ leading to a combined energy cost savings of £878 throughout a 30 year period between the best (+180°) and worst (+45°) orientations of the building was achieved. Highlights: Building orientation contributes to building energy use. BIM is endowed with capabilities that can be used to virtually perform energy analysis. BIM software can accurately predict building energy use.